Evaluating the effective factors for reporting medical errors among midwives working at teaching hospitals affiliated to Isfahan University of Medical Sciences - Fahimeh Khorasani; Marjan Beigi (Iranian Journal of Nursing and Midwifery Research, 2017)
Background: Recently, evaluation and accreditation system of hospitals has had a special emphasis on reporting malpractices and sharing errors or lessons learnt from errors, but still due to lack of promotion of systematic approach for solving problems from the same system, this issue has remained unattended. This study was conducted to determine the effective factors for reporting medical errors among midwives. Materials and Methods: This project was a descriptive cross-sectional observational study. Data gathering tools were a standard checklist and two researcher-made questionnaires. Sampling for this study was conducted from all the midwives who worked at teaching hospitals affiliated to Isfahan University of Medical Sciences through census method (convenient) and lasted for 3 months. Data were analyzed using descriptive and inferential statistics through SPSS 16. Results: Results showed that 79.1% of the staff reported errors and the highest rate of errors was in the process of patients' tests. In this study, the mean score of midwives' knowledge about the errors was 79.1 and the mean score of their attitude toward reporting errors was 70.4. There was a direct relation between the score of errors' knowledge and attitude in the midwifery staff and reporting errors. Conclusions: Based on the results of this study about the appropriate knowledge and attitude of midwifery staff regarding errors and action toward reporting them, it is recommended to strengthen the system when it comes to errors and hospitals risks.